The Impact of Digital Work Culture (Always on and Quick Response) on Workarounds Behavior among Healthcare Workers at Rumah Sehat Terpadu (RST) Dompet Dhuafa Hospital - Rima Febrianti; Kabul Wahyu Utomo (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to explore the dynamics of digital work culture and its impact on the professional practices of healthcare workers at Rumah Sehat Terpadu Dompet Dhuafa Hospital (RS RST DD), focusing on the principles of always on and quick response. Using a qualitative approach with thematic analysis, the study draws on in-depth interviews with 12 participants, including healthcare professionals (doctors, nurses, midwives, and pharmacists), administrative staff, SKDP staff, medical record officers, as well as heads of units and departments. The findings reveal that digitalization enhances coordination efficiency and clinical decision-making. Four main themes emerged: Perceptions of digital work culture characterized by always on and quick response patterns; practices of digital technology utilization; the emergence of workaround behaviors as adaptive responses to system barriers; and the impact of digitalization on professional balance and humanistic values.The results indicate that digital work culture improves efficiency, collaboration, and team responsiveness in patient care. However, the constant expectation to stay connected and responsive also generates psychological pressure, emotional exhaustion, and a decline in empathetic interactions between healthcare workers and patients. Within a value-based institutional context, this phenomenon underscores the urgent need for a humanistic and spiritual design of digital work systems one that not only prioritizes efficiency but also preserves empathy, meaningful communication, and the spirit of service as an act of worship. This study emphasizes the importance of organizational policies that promote digital literacy, healthy work boundaries, and the preservation of humanistic values in healthcare services.